The impact of medulloblastoma-derived extracellular vesicles on the development of primary cortical neurones - McCann, Sophie (2024)
Even though paediatric brain tumour survivors are more likely to be diagnosed with a neurodevelopmental or major psychiatric disorder later in life (Hsu et al., 2023), how tumour cells communicate with and alter the development of cortical neurones is poorly understood. One potential mechanism may be intercellular signalling mediated by the secretion of extracellular vesicles (EVs) by cancerous cells within the brain. EVs are small lipid vesicles that can contain proteins, lipids and RNA and have been shown to mediate intercellular signalling between peripheral cancer cells and neuronal models, promoting neurite outgrowth (Amit et al., 2020; Kovacs et al., 2020; Lucido et al., 2019; Madeo et al., 2018). However, it is unknown whether EVs derived from paediatric medulloblastoma cells have a similar effect on mouse primary cortical neurones.